CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE: ANALISIS ETIKA BISNIS DAN TATA KELOLA PERUSAHAAN DI INDONESIA - Cindy Aulia Zalyanti; Ahmad Wahyudi Zein (CV. Adiba Aisha Amira, 2026)
This research aims to analyze the relationship between Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) in the context of business ethics implementation in Indonesia. Through a qualitative approach and descriptive analysis, this research identifies various relevant literature sources to explore the concept of CSR, GCG principles, and implementation challenges. CSR in Indonesia has become a legal obligation since the enactment of Law No. 40 of 2007 and strengthened by Government Regulation No. 47 of 2012. This research discusses the theoretical foundation of CSR built on Carroll's Pyramid Model, the Triple Bottom Line concept, and Stakeholder Theory. The results show that effective CSR governance is an essential bridge between a company's external responsibilities and GCG's internal management framework. Although CSR implementation can improve corporate reputation and support business sustainability, challenges such as greenwashing practices, weak supervision, and low CSR literacy still need to be addressed. Business ethics is an important foundation for effective CSR and GCG implementation, where the principles of transparency, accountability, responsibility, independence, and fairness must underlie every program to achieve long-term sustainability